Circulating micronutrient levels and respiratory infection susceptibility and severity: a bidirectional Mendelian randomization analysis - Wei, Zhengxiao; Xiong, Qingqing; Liang, Li; Wu, Zhangjun; Chen, Zhu (Frontiers in Nutrition, 2024)
Background Limited and inconclusive data from observational studies and randomized controlled trials exist on the levels of circulating micronutrients in the blood and their association with respiratory infections. Methods A Mendelian randomization (MR) analysis was conducted to assess the impact of 12 micronutrients on the risk of three types of infections [upper respiratory tract infections (URTI), lower respiratory tract infections (LRTI), and pneumonia] and their 14 subtypes. This study utilized a bidirectional MR approach to evaluate causal relationships and included a range of sensitivity analyses and multivariable MR to address potential heterogeneity and pleiotropy. The threshold for statistical significance was set at p < 1.39 × 10−3. Results Meta-analysis revealed that higher levels of circulating copper were significantly associated with a reduced risk of URTI (odds ratio (OR) = 0.926, 95% CI: 0.890 to 0.964, p = 0.000195). Additionally, copper demonstrated a suggestive association with a reduced risk of LRTI (p = 0.0196), and Vitamin B6 was nominally associated with a reduced risk of pneumonia (p = 0.048). Subtype analyses further indicated several suggestive associations: copper reduces the risk of acute pharyngitis (p = 0.029), vitamin C increases the risk of critical care admissions for pneumonia (p = 0.032) and LRTI (p = 0.021), and folate reduces the risk of viral pneumonia (p = 0.042). No significant connections were observed for other micronutrients. Conclusion We observed a genetically predicted potential protective effect of copper in susceptibility to upper respiratory infections. This provides new insights for further research into the role of micronutrients in the prevention and treatment of infection.